1999
DOI: 10.1007/s002770050471
|View full text |Cite
|
Sign up to set email alerts
|

A case of thrombotic thrombocytopenic purpura in an adult treated with vincristine

Abstract: The case of a woman with thrombotic thrombocytopenic purpura refractory to prolonged treatment with plasma exchange and steroid treatment is described. The addition of vincristine yielded a complete response, which has been maintained for 9 months up to the time of this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
5
0
4
Order By: Relevance
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
“…Successful vincristine use has been described in various small studies and case reports, usually as a rescue therapy in refractory TTP [17,[24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…1 Kinetics of platelet count and serum LDH value in a responding patient several reports on the use of VCR for TTP have appeared in the literature. However, most of these described very small series or anecdotal patients; in addition, the schedule of VCR adopted in the different studies varied considerably [3,9,12]. The two largest series were published by Bobbio-Pallavicini et al in 1994 [1] and Mazzel et al in 1998 [4].…”
Section: Discussionmentioning
confidence: 99%
“…La mise en oeuvre des deux échanges plasmatiques par jour chez les patients atteints de PTT ne répondant pas au traitement de première ligne a été proposée par certains auteurs [30]. L'apport de plus grandes quantités de plasma exogène pourrait en effet être nécessaire chez les patients ayant une inhibition forte d'ADAMTS13 dans le plasma.…”
Section: éChanges Plasmatiques Biquotidiensunclassified